Violet Archer's Formative Years: A Bibliographical Catalogue of Her Compositions, 1932–43 - Whittle, James (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1995)
This chronological catalogue of Violet Archer's earliest completed compositions, including works written from 1932 to 1943, is based on manuscripts in her possession and on deposit at the University of Calgary Library, as well as published scores and reproductions of manuscripts in the University of Alberta Library and the libraries of the Canadian Music Centre. It provides the date of composition for each work and summarizes the supporting evidence, including dates found on manuscripts, the types of paper used, entries on lists of works compiled by the composer, and dates of first and early performances. Also included are the medium of performance of each work, a list of movements, the source of any text, and the location of scores and recordings.